2006
DOI: 10.1185/030079906x112660
|View full text |Cite
|
Sign up to set email alerts
|

Allergy medication in Japanese volunteers: treatment effect of single doses on nocturnal sleep architecture and next day residual effects

Abstract: These findings suggest that a single nocturnal dose of fexofenadine has advantages over the first-generation antihistamine chlorpheniramine, being free of disruption of night-time sleep and detrimental effects on cognitive performance the next day. It is likely that this advantage will remain with chronic ingestion, but this would need to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 28 publications
1
38
0
2
Order By: Relevance
“…According to the PSQI, two participants in the TBI Sleep group and three participants in the non-TBI Sleep group reported using over-the-counter sleep aids within the last month. However, we are unaware whether participants used over-the-counter antihistamines, which increase REM latency and reduce REM 77 , during the day of testing. If a greater proportion of TBI individuals were on antihistamine medication during the day of testing, sleep architecture could have been impacted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…According to the PSQI, two participants in the TBI Sleep group and three participants in the non-TBI Sleep group reported using over-the-counter sleep aids within the last month. However, we are unaware whether participants used over-the-counter antihistamines, which increase REM latency and reduce REM 77 , during the day of testing. If a greater proportion of TBI individuals were on antihistamine medication during the day of testing, sleep architecture could have been impacted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…19 -21 The residual effects of poor sleep, including impairment of attention, vigilance, working memory, and sensory-motor performance, are still present the next morning. 20,22 The detrimental central nervous system effects of first-generation H 1 -antihistamines on learning and examination performance in children and on impairment of the ability of adults to work, drive, and fly aircraft have been reviewed in detail in a recent review. 23 The use of first-generation H 1 -antihistamines in young children has recently been brought into question.…”
Section: First-generation H 1 -Antihistaminesmentioning
confidence: 99%
“…3 The main concerns are their sedative properties and interference with rapid eye movement sleep. 3,4 Studies have shown poorer school performance in children with allergic rhinitis treated with sedating antihistamines, compared to children treated with non-sedating antihistamines and healthy children. 5 Sedating antihistamines have been found to be a cause of aviation accidents.…”
Section: Avoid Sedating Antihistaminesmentioning
confidence: 99%